Review Article: The Effectiveness of Avocado Seed Starch (Persea Americana Mill) As An Excipients in Tablets Formulation - Wardiyah Wardiyah; Tashya Putri Maulana; Ulya Safrina (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
Avocado consists of pericarp (husk), mesocarp (flesh), and endocarp (seed). In avocado seeds there is a fairly high starch content, which is around 80.1% with amylose content of 43.3% and amylopectin of 36.8%. Starch is defined as a natural polymer consisting of a structure composed of amylopectin and another structure called amylose. Amylose content has properties that are easy to absorb water and amylose content can have excellent swelling power in the tablet crushing process. This allows avocado seeds as an alternative source of starch which can be an excipient in tablets. The research explored the effectiveness of avocado seed starch (Persea americana Mill) as an excipient in tablet formulations based on research that has been done. The method of the research is using secondary data obtained from literature studies, which were analyzed by bibliographic annotation by searching and analyzing data related to the effectiveness of avocado seed starch as an excipient. The data collection technique in this research is in the form of a review of published scientific journals, national and international journals. Analysis of the physical and chemical properties of avocado seed starch showed that avocado seed was able to become an excipient. Several studies also showed that avocado seed starch used as a disintegrant and binder in tablet formulations had an optimum concentration of 10%. In addition, avocado seed starch can also be used as an active substance in tablets.